Misinterpretations of the Conception of Psychoanalysis According to Merleau-Ponty - Daniel Cardozo Severo (Critical Hermeneutics)
This article is part of ongoing research on Merleau-Ponty’s interpretation of Psychoanalysis. The study proceeds from the thesis that the philosopher has an original intuition, which reveals important and innovative points to Philosophy and Psychoanalysis. The work presented here addresses one of the courses taught by Merleau-Ponty at the Sorbonne from 1949 to 1952 that deals with the adult’s view of the child. On this subject, the philosopher presents the limits of the current philosophical and scientific conceptions, and concerning the purpose of our study, he presents misconceptions, not only about the child but about Psychoanalysis; interpretations of Freudian concepts that contradict what is original and innovative in Psychoanalysis, and how this generates a misconception about the child, reducing Psychoanalysis to a reactionary theory.